2015
DOI: 10.19184/jauj.v13i2.1567
|View full text |Cite
|
Sign up to set email alerts
|

Modifikasi Pembiayaan Salam Dan Implikasi Perlakuan Akuntansi Salam

Abstract: Tinjauan teoritis ini bertujuan untuk membangun solusi untuk menjadikan akad salam sebagai salah satu produk pembiayaan yang applicable, bankable, serta marketable untuk diterapkan di industri perbankan syariah. Hasil dari tinjauan teoritis ini menunjukan bahwa masalah tidak diterapkannya akad salam diperbankan syariah diantaranya adalah; (1) Kekhawatiran pihak bank atas kecurangan atau gagal panen petani; (2) Resiko yang melekat pada akad salam cukup besar; (3) Kurangnya sosialisasi mengenai akad salam terhad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Factors influencing consumer behavior, according to Kotler (2000) as referenced in (Ningsih, 2015), include several elements: cultural factors, social factors, personal factors, and psychological factors.…”
Section: Consumer Behaviormentioning
confidence: 99%
“…Factors influencing consumer behavior, according to Kotler (2000) as referenced in (Ningsih, 2015), include several elements: cultural factors, social factors, personal factors, and psychological factors.…”
Section: Consumer Behaviormentioning
confidence: 99%
“…Auditors are responsible for the interests of stakeholders, particularly investors and public trust, resulting in the independent, objective, and relevant audit quality. Ningsih and Yaniartha (2013) state that time budget pressure has a significant negative effect on audit quality. Furthermore, Nirmala et al (2013) also found that time budget pressure has a significant negative effect on audit quality.…”
Section: Relationship Between Time Budget Pressure and Audit Qualitymentioning
confidence: 99%
“…Meanwhile, according to research by Futri and Juliarsa (2014), auditor professionalism has no effect on audit quality. Time budget pressure research conducted by research by Ningsih and Yaniartha (2013) shows time budget pressure has a significant negative effect on audit quality. Nirmala et al (2013) research also supports the results of previous studies, namely that time budget pressure has a significant negative effect on audit quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akan tetapi, masih terdapat beberapa permasalahan terkait dengan penerapan akad salam sehingga sampai dengan saat ini belum juga dapat terealisasi. Permasalahan utama pada penerapan pembiayaan salam tersebut disebabkan oleh tingginya resiko bagi pihak bank akibat kredibilitas keuangan petani dan faktor alam yang sangat memengaruhi hasil panen (Ningsih, 2015;Adnan, Revisa, dan Faiq, 2016). Sebenarnya penyebab utama timbulnya resiko tersebut adalah perbedaan pemikiran antara bank syariah dan petani, dimana pembiayaan salam berlogika uang sedangkan petani berlogika mekanisme alam.…”
Section: Prinsip Keserasian (Principle Of Harmony) Dalam Tasbihunclassified